A morphology-based cladistic analysis of Digitaria (Poaceae, Panicoideae, Paniceae) - Vega, Andrea Susana (2009)
A phylogenetic analysis was performed on 67 species of Digitaria belonging to four subgenera and 26 of the 32 sections recognized in Henrard's monograph. The analysis was based on 113 discrete and six continuous morphological characters. In the resulting topologies the genus Digitaria was monophyletic. In spite of the low support for most groupings, several clades were recovered. The subdivision of Digitaria in the four subgenera proposed by Henrard was not supported since the large subgenus Digitaria appears as a paraphyletic assemblage within which the other three subgenera are nested. Nevertheless, the monophyly of some of Henrard's sections was supported. This is the first approach to the phylogeny of Digitaria.